Earnings Inequality and Mobility in the United States: Evidence from Social Security Data since 1937* - Kopczuk, Wojciech; Saez, Emmanuel; Song, Jae (Quarterly Journal of Economics, 2010)
This paper uses Social Security Administration longitudinal earnings micro data since 1937 to analyze the evolution of inequality and mobility in the United States. Annual earnings inequality is U-shaped, decreasing sharply up to 1953 and increasing steadily afterward. Short-term earnings mobility measures are stable over the full period except for a temporary surge during World War II. Virtually all of the increase in the variance in annual (log) earnings since 1970 is due to increase in the variance of permanent earnings (as opposed to transitory earnings). Mobility at the top of the earnings distribution is stable and has not mitigated the dramatic increase in annual earnings concentration since the 1970s. Long-term mobility among all workers has increased since the 1950s but has slightly declined among men. The decrease in the gender earnings gap and the resulting substantial increase in upward mobility over a lifetime for women are the driving force behind the increase in long-term mobility among all workers.